Electrochemical studies on carbon dioxide corrosion and its inhibition. - Tan, Yong-jun (Curtin University, 1996)
This thesis mainly concerns the application of electrochemical impedance spectroscopy (EIS) and electrochemical noise analysis (ENA) to the study of CO(subscript)2 corrosion of mild steel and its inhibition. The primary focus is on the use of EIS and ENA to monitor inhibitor film performance and to evaluate inhibitor film persistency.EIS was shown to be a suitable technique to study CO(subscript)2 corrosion product scale, and inhibitor films. The formation and deterioration of protective scales and inhibitor films is found to be accompanied by characteristic spectral changes and a rapid change in electrode impedance. EIS data were used to calculate corrosion related parameters such as the resistances and capacitances of inhibitor layers, and the charge transfer resistance and double layer capacitance. These parameters were used to analyse inhibitor mechanisms, determine corrosion rates and the persistence of inhibitor films.ENA is also a suitable technique to monitor the formation and deterioration of inhibitor films. It has the advantage of being able to monitor rapid processes which occur within one second. Several technical and theoretical developments were made in this thesis including the development of a new method of instantaneous corrosion rate measurement to study fast corrosion processes (the continuous noise resistance calculation method). Experimentally, the noise resistance was confirmed to be similar to linear polarisation resistance in the systems studies. The theoretical background and the advantages and disadvantages of the ENA technique are also discussed.Corrosion product scales formed under different conditions were investigated using EIS and surface analysis techniques. Temperature, pressure and exposure time were confirmed to be the important factors influencing the degree of protection given by the scale. The morphology of corrosion scales showed an obvious correlation to their protective ability. Electron microscopy revealed two types of crystal structures on corroded steel coupons. The smaller crystals associated with one of these structures was found to contribute most to corrosion protection.Several typical CO(subscript)2 corrosion inhibitors, including an imidazoline and a quaternised amine, were studied by EIS. A multi-layer model was employed to explain the EIS characteristics and self-repairing ability of imidazoline films. A quaternised amine film is most probably a physically or electrostatically adsorbed molecular layer which forms rapidly and desorbs easily.The deterioration of films, formed by commercial batch treatment inhibitors, was found to occur in three stages which were indicated or characterised by Bode phase-angle plots. A method to determine inhibitor film persistency was developed. This method is based on determining the three stages of inhibitor film deterioration, and the continuous measurement of corrosion rate, which is accessible at the second and third stages of film deterioration.